Copper bioleaching from sulphided minerals with high levels of pyrite and arsenopyrite - Arias Arce, Vladimir (2015)
The study was carried out with isolated strains of acid drainage and consisted of processing of highly mineralized copper sulphides that mainly contained 45.30% pyrite and 13.12% arsenopyrite. Bioleaching was carried out in 500 ml flasks, where 300 ml of 9k medium, 30 ml of bacterial inoculum (10% V / V) of 7.05x107 Cell / ml and various amounts of FeSO4.7H2O were added. The pH was regulated to 1.8 and they were subjected to platform agitation with 150 RPM at ambient temperature of 20 ° C on average. The tests were carried out in three successive stages at different concentrations of ferrous salt. In the first stage, 72.64% copper was obtained with 6 g / l of FeSO4.7H2O in 22 days. In the second stage, 85.6% of copper was achieved in the absence of the ferrous salt. Greater bacterial growth was also achieved with 15 g / l FeSO4.7H2O and 25.62% copper recovery in 24 days of leaching; In addition, the existence of a direct relationship between the increase in bacterial density and the recovery of copper from the sulphided mineral is determined. In the third stage, 89.38% of copper is recovered in the absence of the ferrous salt and in just 20 days of bioleaching.